Plural Policing in Papua New Guinea: More Than the Sum of Its Parts? - Dinnen, Sinclair (Journal of contemporary criminal justice, 2022)
Scholars increasingly acknowledge that policing involves multiple actors and diverse institutional arrangements. Although the global expansion of private security has prompted much of the current interest in plural policing in the Global North, relatively little attention has been paid to this phenomenon in the Global South despite the manifestly plural character of policing in many such countries. This article examines plural policing in Papua New Guinea (PNG) in the Southwest Pacific. Policing in PNG involves a bewildering array of different actors and institutional forms, ranging from transnational police to unofficial urban settlement committees. Investigating the shifting pattern of pluralization in the context of broader structural changes and the intersections between different providers illuminates how policing actually works in this socially diverse nation, as well as highlighting some of its implications for state and society in this understudied part of the world.